Approaches to Teaching Early Reading: Whole Language or Phonic Approach? - Didi Sukyadi (TEFLIN Journal: A publication on the teaching and learning of English, 1998)
Abstract: The impacts of the great debate on early reading instrucÃÂtion, which was started in the late 1960 and early 1970s, remain until today. In our education system, curriculum change also brings about the change of teaching ideology. For teachers, the result sometimes is more threatening than encouraging because they cannot anticipate the quick and inevitable change. They become disempowered and deprived, and that innovation is often difficult to implement. This study aimed to explore the orientation of student teachers and expeÃÂrienced teachers towards reading instruction, namely phonic, skills, and whole language approach. This involved 30 primary student teachers of an Institute of Education in London and 30 experienced teachers teaching at Year 1 and 2 London inner city primary schools. Each of the respondents was sent a questionnaire, and asked to answer an open ended question concerning the best approach of teaching reading. The results revealed that in general there was no difference in teaching reading orientation between student teachers and experienced teachers. Both of them tend to believe that there was no single best method. The competing approaches are seen as compleÃÂmentary. Any approach chosen should take into account child develÃÂopment, the nature of reading and environmental support. The impliÃÂcations of these findings for teacher empowerment are discussed.